Pengembangan Aplikasi Life Cons Untuk Mencegah Pelecehan Seksual Verbal (Catcalling) Pada Siswa : Developing The Life Cons Application To Preventif Verbal Sexual Harassment (Catcalling) of Students - Agussalim; Abdul Saman; Sahril Buchori (JURKAM: Jurnal Konseling Andi Matappa, 2025)
This research focuses on developing an educational media application called "LIFE CONS" as a response to the increasing prevalence of verbal sexual harassment (catcalling) in senior and vocational high schools (SMA/SMK) in Makassar City. The objectives of this study are: 1) To identify the prototype needs of the Life Cons application as an information service to prevent sexual harassment (catcalling) among students in SMA/SMK across Makassar City; and 2) To determine the level of validity and practicality of the Life Cons application as an information service for the same purpose. This study employed a Research and Development (R&D) approach using the ADDIE model, beginning with a needs analysis through questionnaires distributed to 34 students and interviews with school counselors (BK teachers) at SMAN 3 and SMKN 10 Makassar. The results indicated an urgent need for a user-friendly, informative, engaging medium that maintains the confidentiality of users. Based on these findings, a prototype of the "LIFE CONS" application was designed, featuring an information homepage, educational materials in the form of articles, videos, and comics, a secure incident reporting feature, and a user guide. The application was validated by two guidance and counseling experts and two educational technology experts, resulting in ratings from "Good" to "Very Good," indicating its conceptual and technical validity. Practicality testing involved BK teachers and 60 students (30 from SMA and 30 from SMK), who gave highly positive responses. These findings confirm that the "LIFE CONS" application is easy to use, highly beneficial, and feasible for implementation as a guidance and counseling service tool to prevent catcalling in schools.